(3GdJYQja HGdTjN eMeO GdNQTis - (3eMeO GdLeGdj GdeZQHjs
(3ChdgG (B:s
(3Cbhd (B: (3gh GdTjN GdEeGe GdTgjQ fSHg hfSH YUHJg s
(3BNQgG (B:s
(3eGJ ai UHjMI jhe GdCMO SfI hGMO heGFI hCda , hOaf eY hGdOg hbO PcQg GdTjN CMeO Hf bGSe GdJejei GdHhfi ai CQLhRJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs